Causal association between mTOR-dependent circulating protein levels and central precocious puberty: a Mendelian randomization study - Ying, Yuanxiao; Yu, Ze; Wu, Liping (Frontiers in Endocrinology, 2024)
The mechanistic target of rapamycin (mTOR) signaling pathway has a significant effect on central precocious puberty (CPP). However, the causality between mTOR-dependent circulating protein levels and CPP is still unclear. Our aim is to assess the effects of seven mTORdependent circulating protein levels on CPP using Mendelian randomization (MR).Methods: Instrumental variables (IVs) for mTOR-dependent circulating protein levels were retrieved from the proteomics-GWAS INTERVAL study and eQTLGen. The summary-level genetic datasets for CPP outcome were obtained from the FinnGen Consortium. Inverse-variance weighted (IVW) was used as the primary method and the pleiotropy, heterogeneity and robustness of the analyses were detected as sensitivity analysis. Positive exposures in the discovery cohort would be revalidated in the validation cohort.This two-sample MR study revealed a causal association between eIF4G level in plasma and CPP in both discovery cohort (IVW: OR = 0.45, 95% CI = 0.22-0.91, p = 0.026) and validation cohort (IVW: OR = 0.45, 95% CI = 0.24-0.85, p = 0.014).There was a causal association between eIF4G level in plasma and CPP. Whether eIF4G can be used for the prevention or treatment of CPP needs to be explored in further studies.